Root NRT, NiR, AMT, GS, GOGAT and GDH expression levels reveal NO and ABA mediated drought tolerance in Brassica juncea L. - Seema Sahay (Nature Portfolio, 2021)
Abstract Little is known about the interactive effects of exogenous nitric oxide (NO) and abscisic acid (ABA) on nitrogen (N) metabolism and related changes at molecular and biochemical levels under drought stress. The present study highlights the independent and combined effect of NO and ABA (grouped as “nitrate agonists”) on expression profiles of representative key genes known to be involved in N-uptake and assimilation, together with proline metabolism, N–NO metabolism enzyme’s activity and nutrient content in polyethylene glycol (PEG) treated roots of Indian mustard (B. juncea cv. Varuna). Here we report that PEG mediated drought stress negatively inhibited growth performance, as manifested by reduced biomass (fresh and dry weight) production. Total N content and other nitrogenous compounds (NO3 −, NO2 −) were decreased; however, NH4 +, NH4 +/ NO3 − ratio and total free amino acids content were increased. These results were positively correlated with the PEG induced changes in expression of genes and enzymes involved in N-uptake and assimilation. Also, PEG supply lowered the content of macro- and micro-nutrients but proline level and the activity of ∆1-pyrroline-5-carboxylate synthetase increased indicating increased oxidative stress. However, all these responses were reversed upon the exogenous application of nitrate agonists (PEG + NO, PEG + NO + ABA, and PEG + ABA) where NO containing nitrate agonist treatment i.e. PEG + NO was significantly more effective than PEG + ABA in alleviating drought stress. Further, increases in activities of L-arginine dependent NOS-like enzyme and S-nitrosoglutathione reductase were observed under nitrate agonist treatments. This indicates that the balanced endogenous change in NO and ABA levels together during synthesis and degradation of NO mitigated the oxidative stress in Indian mustard seedlings. Overall, our results reveal that NO independently or together with ABA may contribute to improved crop growth and productivity under drought stress.